Growth dynamics of mold-yeast and bacteria during the production process of saga tauco [Adenanthera pavonina]. Issue 1 (May 2021) - Amar, A; Makosim, S; Sukotjo, S; Ahadiyanti, N; Weisman, E
Abstract: Sagabean as a plant protein source, Sagabean has not been used by society. Several studies regarding Sagabean being a food product have been initiated. Sagabean can be used as tauco. The study was to observe the growth dynamics of microbe in Sagabean tauco during the production process. The manufacturing of Sagabean tauco was the same as making of soybean tauco. It was soaking, boiling pealing, soaking overnight, followed by steaming, and inoculating with tempe starter. Saga tempe was crushed then mixed with glutinous rice flour that had been roasted. After drying, it was put in the brine solution for fermentation. The observation were total microbes, total yeast-mold, total lactic acids bacteria, total protein, total dissolved solids, total acid, pH value, and ash content. The aim of this research was to see the relationship between the presence of microorganisms and their metabolic processes during tauco production. The result showed that the total number of microbes had increased during the fermentation process until a certain period, then it was constant and decreased according to the growth curve of microorganisms in general. For yeast and molds being relatively fluctuating and tending to increase. This seemed to relate to the presence of halophilic microorganisms in the product. Regarding the pH of the product during fermentation, it had a relevant value, while the ash content experienced a fluctuating value. If it had been related to the presence of microorganisms, the metabolism of the existing microorganisms would have affected the chemical properties of the saga tauco.